First-in-human trial of the safety, pharmacokinetics and immunogenicity of a PEGylated anti-CD40L antibody fragment (CDP7657) in healthy individuals and patients with systemic lupus erythematosus. (September 2015) - Tocoian, A; Buchan, P; Kirby, H; Soranson, J; Zamacona, M; Walley, R; Mitchell, N; Esfandiari, E; Wagner, F; Oliver, R
Objective: The objective of this paper is to investigate the safety, pharmacokinetics (PK) and immunogenicity of CDP7657, a PEGylated anti-CD40L antibody fragment, in healthy individuals and patients with systemic lupus erythematosus (SLE). Methods: This randomized, double-blind, single-dose, dose-escalation phase I study consisted of two parts. In part 1, 28 healthy individuals received CDP7657 IV (0.004–5 mg/kg) or placebo. In part 2, 17 patients with SLE received CDP7657 IV (5–60 mg/kg) or placebo. The CDP7657:placebo ratio was 3:1. Results: Adverse events (AEs) were reported by 76% of healthy individuals and 100% of patients with SLE treated with CDP7657; most were mild or moderate in intensity. Two healthy individuals reported serious AEs (SAEs), one of which was considered treatment related (infusion-related reaction; 5 mg/kg cohort). One patient with SLE (60 mg/kg cohort) experienced three SAEs, one of which was considered treatment related (herpes zoster infection). No thromboembolic events were reported. CPD7657 exposure increased in a dose-proportional manner. Low anti-CDP7657 antibody titres were detected in the majority of CDP7657-treated participants with no apparent impact on the PK of CDP7657. Conclusion: Single doses of CDP7657 showed predictable PK in healthy individuals and patients with SLE and were well tolerated, with no safety signals of concern. These findings support further investigation of CDP7657 as a therapy for SLE.